Vastus Lateralis Architecture Changes During Pregnancy – A Longitudinal Study - Bey, Marie Elena; Marzilger, Robert; Hinkson, Larry; Arampatzis, Adamantios; Legerlotz, Kirsten (Frontiers in Physiology, 2019)
While the incidence of falls has been described to increase with pregnancy, the mechanism behind this is unclear. Pregnancy associated changes in lower extremity muscle strength could be a possible factor influencing injury risk. Thus, the aim of this longitudinal study was to investigate muscle strength and architectural properties of the lower limbs in different stages of pregnancy and postpartum. In nineteen pregnant women (30±4years) and fifteen non-pregnant controls (28±4years) muscle strength and architectural properties of the vastus lateralis muscle were assessed combining dynamometry, ultrasound, kinematic and electromyographic measurements. Body mass and body composition were determined using bioimpedance analysis. In the pregnant women, the measurements were conducted in the 16±4th (EP) and 29±4th week of pregnancy (LP) as well as in the 32±9th week postpartum (PP). Muscle thickness and pennation angle of the fascicles significantly increased at LP, while muscle strength remained constant during and after pregnancy. Body mass, skeletal muscle mass, fat mass, intracellular and extracellular water also peaked at LP. Postpartum values did not differ from the controls. Changes in the muscle properties were not related to changes in body mass and body composition. Conditions during pregnancy promote changes in the vastus lateralis architecture indicating muscle hypertrophy. However, pregnancy did not increase muscle strength while body mass progressively increases. Therefore, in the event of balance perturbations pregnant women may not be able to meet the requirements for the increased physical demand.